How did the origin of herbivory in tetrapods expand the food webs? (Zubía, 2024)
Herbivory is key in trophic webs, but it took a while for it to appearin tetrapods. Comparing the dental geometry of the taxa from Linton, USA,fossil site in which the first amniote capable of consuming plants appeared,we show that vegetables could have been more involved in their diets thanwhat was previously thought. Our results indicate that insectivory is thepreceding step to omnivory, based on the similar dentitions and sizes ofthe taxa with these diets, in addition to the availability of insects and plants.They also show the stability of this ecosystem and the fact that omnivoryallowed the appearance of bigger predators, as well as suggesting an important role for the competition between different taxa. This study indicatesthat the ecosystem of Linton was more similar to the modern ones than itwas previously thought.